Sejarah Teks - Naskah (An-Nash Wa An-Nuskhah) Dalam Tradisi Arab-Islam - shofin sugito (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2015)
Abstract The Article describes about the historical phenomenon of texts and its manuscript (corpus) in the Arabic-Islamic culture. It focuses on the chronological trip of the writing tradition belonging to Arab-Islam; from the text on camal’s skin into the text on letters. Is there some changings and phenomenons in every Arabian’s inovations? How much useful for us to study this chronology? Thus, the article aims to explain, discus and highlight the chronological trip Arabic-Islamic Texts and its manuscripts. The method of this article is using literature reviews from classical and contemporary islamic books. It gives the new horizan of thinking about the writing tradition of Arabian-Moslems and its studies. Keywords: naskah, tradisi, makhtuthat, al-waraq, al-warraqun….etc.